Time-dependent antioxidative responses of ramie (Boehmeria nivea (L.) Gaudich) to moderate cadmium stress and its up-regulation mechanism by spermidine antioxidant. Issue 93 (11th October 2015) - Zhou, Lu; Liu, Yunguo; Hu, Xi; Zeng, Guangming; Wang, Yaqin; Hu, Xinjiang; Zhou, Yaoyu; Tan, Xiaofei; Jiang, Luhua; Zeng, Xiaoxia
<x xml:space="preserve">Abstract</x> Cadmium (Cd) is present in soil and water at low concentrations that can be harmful to the biota.